A New Non-invasive Method for Collecting DNA From Small Mammals in the Field, and Its Application in Simultaneous Vector and Disease Monitoring in Brushtail Possums - Emami-Khoyi, Arsalan; Agnew, Thomas W.; Adair, Matthew G.; Murphy, Elaine C.; Benmazouz, Isma; Monsanto, Daniela M.; Parbhu, Shilpa P.; Main, Devon C.; Le Roux, Rynhardt; Golla, Tirupathi Rao; Schnelle, Claudia; Alizadeh, Hossein; et al. (Frontiers in Environmental Science, 2021)
Large-scale monitoring of wild populations in remote areas using traditional live-capturing methods is logistically and financially challenging. Devices that can be used to obtain biological material remotely and store it for an extended period have considerable potential to monitor population densities and health status, but their applicability remains largely unexplored. The present study describes a device that collects trace amounts of DNA from the saliva of small mammals that is deposited on the surface of a collection medium (WaxTags®). The device's performance was evaluated on Australian brushtail possums (Trichosurus vulpecula), an invasive pest species and the most significant vector of bovine tuberculosis infective agent (Mycobacterium bovis), under field conditions in Canterbury, New Zealand. The retrieved DNA was used to amplify eight possum-specific microsatellite markers and bacterial 16S rRNA. The design was mechanically robust, and the quality of the recovered DNA was adequate for microsatellite-based identification of individual possums, estimation of population density, and partial reconstruction of their oral microbiomes as a potential indicator of health. Several medically important bacteria, including strains of environmental Mycobacterium sp., were detected. The design can be refined to monitor other animals' populations proactively and provide different levels of information necessary to manage wild populations.